Organizational Effectiveness: Social Capital and Competitive Advantage Approach - Putri, Vini Wiratno; Yuniawan, Ahyar (Jurnal Dinamika Manajemen, 2016)
This study is aimed at developing the model of organizational effectiveness in university through social capital and competitive advantage. The populations of this study are the head of study programs and the structural officials in some Universities in Semarang. In this case, We used Structural Equation Modeling (SEM) in AMOS 21.0 program as the analysis tool. The result of the study and model analysis showed that even though the social capital had significant positive influenced to the competitive advantage in the university, the improvement of social capital and competitive advantage at university could not improve the university organizational effectiveness. Then, between two factors which influenced the competitive advantage (internal social capital and external social capital), it is obtained that external social capital got the dominant influenced factor to competitive advantage. The managerial implication suggested the policies should focus on improving the quality of cooperative relationships with external parties in the university.Â Tujuan dari penelitian ini adalah membangun model efektifitas organisasi pada perguruan tinggi melalui modal sosial dan keunggulan bersaing. Populasi dalam penelitian ini adalah ketua program studi maupun pejabat struktural pada perguruan tinggi di Semarang. Alat analisis data yang digunakan adalah Structural Equation Modelling (SEM) pada program AMOS 21.0.Hasil pengujian dan analisis model menunjukkan bahwa pada meskipun modal sosial memiliki pengaruh positif signifikan terhadap keunggulan berasingn pada perguruan tinggi namun peningkatan modal sosial dan keunggulan kompetitif pada perguruan tinggi belum mampu meningkatkan efektifitas organidsasi perguruan tinggi tersebut. Selanjutnya diantara kedua faktor yang mempengaruhi keunggulan bersaing (internal social capitaldan external social capital), didapatkan bahwa external social capital merupakan faktor yang paling dominan pengaruhnya terhadap keunggulan bersaing. Implikasi manajerial yang dapat disarankan oleh penelitian ini adalah kebijakan yang menitikberatkan pada peningkatan kulitas hubungan kerjasama dengan pihak eksternal pada perguruan tinggi.JEL Classification: L, L2, L20